Microstructure and mechanical properties of twin-wire arc sprayed Ni-Al composite coatings on 6061-T6 aluminum alloy sheet - Wang, Ji-xiao; Liu, Jing-shun; Zhang, Lun-yong; Sun, Jian-fei; Wang, Zhi-ping (International journal of minerals, metallurgy and materials, 2014)
We have systematically studied the microstructure and mechanical properties of Ni-5wt%Al and Ni-20wt%Al composite coat- ings fabricated on 6061-T6 aluminum alloy sheet by twin-wire arc spraying under different experimental conditions. The abrasive wear be- havior and interface diffusion behavior of the composite coatings were evaluated by dry/wet rubber wheel abrasive wear tests and heat treat- ment, respectively. Experimental results indicate that the composite coatings exhibit features of adhesive wear. Besides, the Vickers micro- hardness of NiA1 and Ni3AI intermetallic compounds is relatively larger than that of the substrate, which is beneficial for enhancing the wear resistance. With the increase of annealing temperature and time, the interface diffusion area between the Ni-Al coating and the substrate gradually expands with the formation of NiAl3 and Ni2Al3 phases, and is controlled by diffusion of aluminum atoms. The grain growth ex- ponent n of diffusion kinetics of the Ni-Al coating, calculated via a high-temperature diffusion model at 400, 480, and 550℃, is between 0.28 and 0.38. This satisfies the cubic law, which is consistent with the general theoretical relationship of high-temperature diffusion.